Effectiveness of Skin Perfusion Pressure Monitoring during Surgery for an Ischemic Steal Syndrome Associated Refractory Ulcer. Issue 2 (March 2015) - Okubo, Kentaro; Sato, Takashi; Matsubara, Chieko; Tsuboi, Masato; Ishii, Yasuo; Tojimbara, Tamotsu
We describe an 80-year-old man with end-stage renal disease due to type 2 diabetes who had been maintained on hemodialysis for 9 years. He developed refractory ulcers from an abraded wound in the right hand of his access arm. The arteriovenous fistula (AVF) was located between the right brachial artery and the median antecubital vein draining into the cephalic vein and the deep veins close to the elbow. The blood flow of the right brachial artery measured by using Doppler ultrasonography was 920 ml/min. On the contrary, the radial and ulnar arteries were poorly palpable near the wrist, and ultrasonography could not be performed accurately because of a high degree of calcification. The skin perfusion pressure (SPP) of the first finger on the affected side decreased to 22 mmHg. However, the SPP improved to approximately 40 mmHg upon blocking an inflow into the deep vein. According to SPP data, only a communicating branch of the deep vein was ligated, and the AVF itself was preserved. One month after surgery, the skin ulcer healed, and maintenance hemodialysis was performed by using the preserved cephalic vein for blood access. In conclusion, we successfully treated a refractory wound associated with steal syndrome, without terminating the AVF. SPP-guided surgery may be safe and effective to adjust the blood flow in patients with AVF having steal syndrome.